Could Sodium Chloride be an Environmental Trigger for Immune-Mediated Diseases? An Overview of the Experimental and Clinical Evidence - Toussirot, Eric; Béreau, Matthieu; Vauchy, Charline; Saas, Philippe (Frontiers in Physiology, 2018)
Immune mediated diseases (IMDs) are complex chronic inflammatory diseases involving genetic and environmental factors. Salt intake has been proposed as a diet factor that can influence the immune response. Indeed, experimental data report the influence of sodium chloride on the differentiation of naive CD4+ T cells into IL-17 secreting T helper (Th) cells (Th17 cells), by a mechanism involving the serum glucocorticoid kinase-1 (SGK1) that promotes the expression of the IL-23 receptor (IL-23R). The IL-23/IL-23R is critical for pathogenic inflammatory Th17 cell differentiation. Experimental data in murine models of arthritis, colitis and encephalomyelitis corroborate these findings. This manuscript reviews the current knowledge on the effects of sodium chloride on innate and adaptive immunity. We also performed a systematic literature review for clinical studies examining the relationships between salt consumption and the development or the activity/severity of the most common IMDs mediated by the IL-23/Th17 pathway, i.e., rheumatoid arthritis (RA), multiple sclerosis (MS) and Crohn’s disease (CD). Nine studies were found, 4 in RA, 4 in MS and 1 in CD. An association was found between developments of anti-citrullinated protein antibody (ACPA) positive RA in smokers and salt intake, but these results were not confirmed in another study. For MS, no association was observed in paediatric subjects while in adult patients, a link was found between salt intake and disease activity. However, this result was not confirmed in another study. These conflicting results highlight the fact that further evaluation in human IMDs is required. Moreover, physicians need to develop clinical trials with diet interventions to evaluate the impact of low salt intake on disease activity/severity of IMDs.